33.5k views
4 votes
What is the correct answer for this equation: -7(6+8v)=6-8v​

User Lagistos
by
6.6k points

2 Answers

2 votes

Let's solve your equation step-by-step

-7(6+8v)=6-8v

Step 1 :Simplify both sides of the equation

-7(6+8v)=6-8v

(-7)(6)+(-7)(8v) =6+-8v(distribute)

-42+-56v=6+-8v

-56v-42=-8v+6

Step 2 : Add 8v to both sides

-56v-42+8v=-8v+6+8v

-48v-42=6

Step 3: Add 42 to both sides

-48v-42+42=6+42

-48v=48

Step 4: Divide both sides by -48

-48v/-48 =48/-48

Answer: V=-1

.

User Pollitzer
by
6.2k points
4 votes
the answer would be v = -1
User Sesame
by
6.1k points